NEST-SITE CHARACTERISTICS OF YELLOW-LEGGED GREENPIGEON, TRERON PHOENICOPTERA IN A TROPICAL EVERGREEN FOREST PATCHES OF EASTERN ASSAM, INDIA - OINAM SUNANDA DEVI,; RASANTA KUMAR SAIKIA, (The Bioscan, 2012)
Columbidae (pigeons and doves) is one of the most threatened bird families in the world yet it has received relatively little attention for conservation. We surveyed Yellow- legged Green-pigeon at Jeypore Reserve forest to study their nesting habitat and nest-site characteristics during two breeding seasons in 2008 and 2009. Parameters of nest sites were measured and enumerated using specific habitat quantification methods. A total of twenty nest trees were located during the survey and twelve nest-site parameters were measured and analyzed. It was found that nest trees differ significantly from centre trees of non-nest plots in terms of size. There have also been differences in the other nest tree variables such as GBH, height of tree etc of nest plots and centre tree variables of non- nest plots. PCA performed extracted three principal components which explained 74.81% variability. Apart from these, twenty potential nest tree species of Yellow-legged Green-pigeon that occurred in the 0.25 ha plots were identified. Bombax ceiba and Tetramelos nudiflora are the most common tree species among them and their overall occurrence were 4.5 trees/ha and 3.0 tree/ha respectively. Nesting attempts were recorded on 20 nests. Of the total nests located, 60.9% nests were successful as squabs were hatched in these nests while 39.1% were unsuccessful.